Airport design and operation - Kazda, Antonín; Caves, Robert E. (Advances in mergers and acquisitions ;, 2015)
In this third edition the chapters have been enhanced to reflect changes in technology and the way the air transport industry runs. Key topics that are newly addressed include low cost airline operations, security issues and EASA regulations on airports. A new chapter covering extended details about wildlife control has been added to the volume.